Influences of the criminal justice system on use of medications for opioid use disorder: a qualitative study - Taylor, Emmeline; Gray, Caroline; Stimmel, Matthew; Binswanger, Ingrid A.; Morse, Erica; Timko, Christine; Harris, Alex H. S.; Smelson, David; Finlay, Andrea K. (BMC global and public health, 2024)
Background Legal-involved veterans with opioid use disorder (OUD) have lower receipt of medications for opioid use disorder (MOUD) than other veterans served at the Veterans Health Administration (VHA). This qualitative study examined the influence of the criminal justice system on access to MOUD for legal-involved veterans in the U.S. Methods VHA facilities ( n = 14) that varied in their provision of MOUD to legal-involved veterans were selected for qualitative interviews. Interviewees included legal-involved veterans ( n = 18), VHA Veterans Justice Programs Specialists ( n = 15), substance use disorder treatment providers ( n = 5), and criminal justice staff ( n = 12). Team members applied codes to meaningful units of analysis (quotations) in the transcribed interviews. Using a matrix approach, team members created a spreadsheet matrix with codes, facility rate of MOUD, and relevant quotations summarized for each participant. Themes and connections between individual participants and cross-interview concepts were explored. Participants were not asked to provide feedback on the findings. Results Themes identified were as follows: (1) Veterans Treatment Court policies both enhanced and limited MOUD treatment access and utilization among participants; (2) cross-system collaboration strengths and challenges existed; and (3) criminal justice system treatment preferences and policies both enhanced and limited MOUD in jails and prisons. Conclusions The influence of the criminal justice system on MOUD has led to variable access to MOUD for legal-involved veterans. Our findings can help inform recommendations to enhance access to MOUD for veterans within the criminal justice system, including the development of a national database of MOUD education materials for Veterans Treatment Courts, strengthening community-court relationships, allowing individuals to use their own healthcare coverage within jails and prisons and extend Medicaid coverage into criminal justice settings, and applying national quality measures for MOUD to criminal justice settings and develop a national system for tracking these quality measures.